Abscisic Acid and Sulfate Offer a Possible Explanation for Differences in Physiological Drought Response of Two Maize Near-Isolines - Shekoofa, Avat (Plants (Basel), 2020)
The hypothesis was tested that differences in response to water-deficits between low osmotic potential (LOP) and high osmotic potential (HOP) maize (Zea mays L.) near-isolines were associated with differences in transpiration rate sensitivity to abscisic acid (ABA) and/or sulfate. In a series of four experiments, decreases in transpiration rate (DTR) of whole plants and fully expanded leaves were measured in response to treatments of 1.0 µM ABA and 15 mM MgSO(4) singly and in combination following long (2 day) and short (180 min) exposures. There was little evidence that intact plants grown on soil were responsive to the treatments. For hydroponically grown plants subjected to long exposure, there was similarly no response to treatments. Further, the short exposure of hydroponically grown plants to solely ABA or a combination of chemicals resulted in no sensitivity in DTR for either of the near-isolines. On the other hand, when these plants were fed sulfate, the transpiration was stimulated by about 20% for the LOP and 60% for the HOP. Detached leaves proved to be the most sensitive to treatment. Treatment with the two chemicals singly caused essentially equivalent DTR in the two near-isolines. However, treatment with ABA plus sulfate resulted in different DTR between the two near-isolines with values of 65% for the LOP and 16% for the HOP near-isoline. Overall, these results showed that the short exposure treatment of hydroponically grown plants or detached leaves supported the hypothesis of different transpiration rate sensitivities of the near-isolines in response to ABA and sulfate treatments.